A different story of modern economic science - Bazzichi, Oreste; Reali, Fabio (Warszawskie Studia Teologiczne, 2021)
This paper wants to demonstrate a scenario where it is evident that the medieval society, starting from the monasticism of St. Benedict (famous motto of «ora et labora») and continuing with the Franciscan School, conserves many elements and ideas of intellectual interest that have a reverberation still valid for today, especially concerning the relationship of man with the economy. The age of the Late Middle Ages in Europe laid the foundations of modern economic science, giving impulse to quite singular reflections gathered from the interpretation of reality, in a typically «Franciscan» key, grasping in the fraternity (franciscan fraternitas) the anthropological and ontological element for the good living in the communitas and for the integral sustainability, therefore, valid also for the economy. It resulted, in fact, the first economic and commercial lexicon that will spread throughout Europe, by the work of important disciples of St. Francis, who grasped a new «spirit» of making economy, completely original, countercurrent, contradicting the prevailing thesis of Max Weber. But Franciscan humanism still offers, even today, the anthropological, social, and cultural presuppositions for a shift of paradigm within the economic discourse, based on the person with all his inclinations and necessities, presuppositions that are already visible in the experience of the Economy of Communion in Freedom, born on May 29, 1991, among the misery of Brazil, to solve the social and economic problem of this time. This revolution of the late Middle Ages, social and market, which was also intellectual and aimed at facing the poverty and injustice of that time, is still repeated today with new faces, experiences, and theories.